2016
DOI: 10.1080/17458080.2016.1189096
|View full text |Cite
|
Sign up to set email alerts
|

Damage tolerance behaviour of cloisite 15A incorporated recycled polypropylene nanocomposites and bionanocomposites

Abstract: In the present investigation, recycled polypropylene (rPP) used as a matrix was modified by incorporating nanofillers through melt blending technique to prepare a masterbatch of nanocomposites. Untreated sisal fibre and mercerised sisal fibres were further incorporated into the nanocomposites for the preparation of bionanocomposites. Bionanocomposites containing 40 wt% of UT fibre and 5 wt% of MA-g-PP revealed an increase in the tensile strength and modulus to the tune of 27% and 370%, respectively, compared t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 43 publications
0
4
0
Order By: Relevance
“…Furthermore, the quantitative analysis of interfacial adhesion, in prepared nanocomposites from waste polymers, showed a strong interfacial adhesion between the nanoparticles and waste polymers and justified the recycling of polymers via the incorporation of nanoparticles (3). In the last few years, many researchers have used nanofillers to recycle waste PP polymers (4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18). These studies investigating polymer recycling via the incorporation of nanofillers with improved nanocomposites' properties are reported in Table 1.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the quantitative analysis of interfacial adhesion, in prepared nanocomposites from waste polymers, showed a strong interfacial adhesion between the nanoparticles and waste polymers and justified the recycling of polymers via the incorporation of nanoparticles (3). In the last few years, many researchers have used nanofillers to recycle waste PP polymers (4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18). These studies investigating polymer recycling via the incorporation of nanofillers with improved nanocomposites' properties are reported in Table 1.…”
Section: Introductionmentioning
confidence: 99%
“…[10,11] Nanoclay is a highly activated potential filler for resin modification to enhance different properties of natural fiber reinforced bio-resin based composites. [12,13] Very limited scientific reports are available on jute reinforced bio-resin based composite with nanoclay. Iman and Maji examined the effect of nanoclay on soy flour-jute composite and reported that in the presence of nanoclay and glutaraldehyde, soy flour crosslinked with the jute surface to produce a covalent bond.…”
Section: Introductionmentioning
confidence: 99%
“…Fabricated composite (40 wt.% of sisal fiber with PP and 3 wt.% nanoclay) showed mechanical strength of 24 MPa but flexural strength of 63 MPa owing to the high aspect ratio of the nanoclay that participated in effective surface interaction. [12] The primary focus of this research work is to examine the influence of Cloisite 15A on mechanical, morphology, hydrophilic, thermal, and soil-degradation properties of jute-soy composite. Since; both jute, and soy are renewable and biodegradable, their composites should be degradable and may be applied as plastic alternant in automobile, packaging, and furniture sectors.…”
Section: Introductionmentioning
confidence: 99%
“…However, post-consumer polypropylene (often called recycled PCPP) could acquire desired properties by incorporating nanofillers into polymer matrix. 4 Most commonly used nanoparticles to reinforce recycled PP are montmorillonite (MMT), 5 graphene, 6 carbon nanotubes, 78 silica, 910 Boehmite alumina, 11 calcium carbonate (CaCO 3 ), 12 and zinc oxide. 13 Among all nanoadditives, clay is the most preferred one for preparing polymer/layered silicate composites.…”
Section: Introductionmentioning
confidence: 99%